Effect of Tropaeolum Tuberosum "Mashua" (Tropaeolaceae) on gene expression related to spermatogenesis in mouse: Efecto de Tropaeolum Tuberosum "Mashua" (Tropaeolaceae) sobre la expresión génica relacionada a Espermatogénesis en ratón - Gonzales Daga , José (2023)
Introduction: Tropaeolum tuberosum, known as "mashua" is an Andean tuber that holds both economic and nutritional value for low-income populations. It is believed that it affects male fertility because Andean men associate it with impotence and decreased fertility. Studies conducted on rats fed with "mashua" showed that there was a 45% decrease in the testosterone/dihydrotestosterone ratio. The effect of this plant on reproduction is related to its content of isothiocyanates, compounds that covalently bind to proteins, which may be directly or indirectly involved in the spermatogenic process. The purpose of this research was to evaluate the effect of the aqueous extract of "mashua" on spermatogenesis and reproductive physiology of mice. Methodology: In vivo morphofunctional parameters of mouse sperm (spermatogram) were evaluated and the expression of Cytochrome P450 17α-hydroxylase/17,20-lyase, acute steroidogenesis regulatory protein, cyclin, and protamine related to spermatogenesis was quantified. Results: The results indicated that at 7, 14 and 21 days of dosing, the sperm count was affected, as well as their progressive motility (PM), on the other hand, a delay in their maturation was observed. Regarding gene expression, no significant differences were found between the expression of the two genes studied (Cytochrome P450 17α-hydroxylase/17,20-lyase, Cyclin), Conclusion: The effect of "mashua" does not occur at the level of gene expression involved in spermatogenesis, but at the level of its functions as a protein.